Simulating COVID-19 Trajectory in the UAE and the Impact of Possible Intervention Scenarios - Abdulla M. Alsharhan (Advances in Science, Technology and Engineering Systems Journal, 2021)
This paper aims to simulate the current trajectory of the pandemic growth in the UAE; when it is likely to end and at what cost? It also examines the current and additional possible measures to contain the second wave of the pandemic. The method used is a simple Susceptible-Infected-Recovered (SIR) model called covid19_scenarios. The key finding suggests current intervention is 35 – 45% and effective, and based on keeping them, the pandemic curve in the UAE is expected to be flattened around the fourth quarter of 2022 with the maximum saved lives and lowest burden on the healthcare system. In contrast, it can end earlier at the end of the second quarter of 2021 but at a much higher fatality rate and a health system ready with 3,600 intensive care units. It also revealed that country closure has a minor impact, and severe and fatal cases will continue to appear even after vaccinating the whole community.
Keywords: Agent-Based Model; COVID-19 Simulation; UAE; United Arab Emirates; Agent-based simulation